Digitalization of Cultural Villages: Assistance in Optimizing Branding of Wirokerten Village in Realizing a Culturally Independent Village - Kholid, Anwar; Sakir, Sakir; Pribadi, Ulung; Saputra, Rivaldi Alan; Hakim, Rosyid Annafi' (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
The partners of this community empowerment program are the Cultural Village Pioneer institution located in Wirokerten Village, Banguntapan District, Bantul Regency, Yogyakarta Special Region Province. Based on the Focus Group Discussion (FGD), two main problems of the Cultural Village Pioneer were found, namely 1) the lack of branding identity of Wirokeren Cultural Village, and 2) the digitalization management of the Wirokerten Cultural Village Pioneer is not yet optimal. This service uses the Asset-Based Community Development (ABCD) method, which consists of problem identification, program conceptualization, program implementation, monitoring & evaluation, and follow-up plans. In solving the problem, this stage has carried out two activities as follows: 1) Creation of a mascot as a village identity; and 2) Development of social media, particularly Instagram and Website, to optimize digital branding. The mascot designed is a representation of Tumenggung Wirokerti, a respected historical figure in the village, used as a symbol of courage and devotion. In addition, the digitization of Wirokerten Cultural Village was carried out by creating an Instagram account and website that showcase the village's cultural potential. The follow-up to this service program involves strengthening the identity of Wirokerten Cultural Village and increasing brand awareness through collaboration with local or national influencers.